KESALAHAN LEKSIKAL DALAM BAHASA INGGRIS SISWA SEKOLAH DASAR KELAS V: SEBUAH KAJIAN ERROR ANALYSIS - Ida Bagus Gde Nova Winarta (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2016)
ABSTRACT This research was entitled “Lexical Errors in English of Elementary School 5th Grade Students: an Error Analysis Study. Basically language use is something that is very complicated, for example, related to mother tongue, second language, and foreign language. Especially, this is focused on foreign language because such errors occur when learning this language related to the rules of this language. Specifically, this research aimed at understanding two things, such as: (1) lexical use in English and (2) factors causing errors in using lexical in English. Research method applied in this research consists of approach research, kind and data source, method and technique of collecting data, method and technique of analyzing data, and method and technique of presenting the data analysis. Qualitative approach was used in this research and the data source was the observation that was done by the researcher toward Elementary School 5th Grade Students. The method used in collecting data was by using observation method and interview method. Intralingua comparison was used to analyze the classified data. Then, the result of the analysis was presented by using formal and informal method. The discussion of the problems was preceded by an error related to lexical use, basic lexical and universal lexical. Based on the analysis, the researcher found that errors related to basic lexical, such as: errors in word formation, errors in word order, errors in question form, errors in verb form, errors in adjective form, errors in adverb form, errors related to bound morpheme, error in pattern of like + verb -ing, error in pattern before….verb -ing, and gerund error. Then, the cause factors of errors in using lexical and acquiring syntax in English, such as: Intralingua factor and Interlingua factor. From the result and discussion, it could be concluded that the researcher found some errors in using English done by the Elementary School 5th Grade Students, related to lexical. The writer was aware that this research has some limitation or shortage so it is hoped that this research could be continued in order to get better result for the society in general. Key words: errors, lexical.